The savage hour / Elaine Proctor. - Proctor, Elaine (Quercus Editions, 2014)
De Wildt, South Africa. On an oppressively hot day, an elderly doctor is found drowned in the dam on her home farm by her sixteen-year-old granddaughter. She slipped to her death. Bereft, her community remembers a matriarch of fierce spirit, whose talent for healing and instinct for trouble brought solace to the people yet failed her children. But her granddaughter and detective friend come to question the cause of her death - threatening to expose the fractures in the family with one insistent doubt: she did not slip. From this discovery, this loss, ripples of disquiet will spread beyond the family; extending to servants and to farmhands; to the police, hospital and town beyond. All must face the wave that turns them from the course of their lives, or be swept under.